USAGE OF DARK-FIELD IMAGE FOR IDENTIFICATION OF PHASE COMPONENTS OF PIPE STEELS - A. G. Anisovich; S. M. Krasnevskij; M. K. Stepankova (Литьë и металлургия)
The reasons of low impact strength and high temperature of viscous-fragile transition of the basic metal of gas pipe from steel 17G1С are investigated. It is established that high fragility of metal of pipe is caused by release of the cementite extended inclusions at the border perlite-ferrite by metallographic researches with application of methods of light and dark field.